Comparative study of psychiatric patients receiving treatment in tertiary care hospital and in primary health care center - Guruprasad, C.; L., Dayananda Sagar; ., Vishwanatha; H., Chandrashekar (International Journal of Advances in Medicine, 2020)
Background: Integrating mental health services into primary care is the most viable way of closing the treatment gap and ensuring that people get the mental health care they need. Government of Karnataka initiated the Manochaitanya programme to ensure that mental health services at all primary health care centers, community health centers and taluk hospitals on every Tuesday. Its required to know the patient satisfaction in this programme. Methods: This study was conducted over a period of two years, cross-sectionally seen 102 cases from 9 PHC’s that runs psychiatric clinics every Tuesday. This population was compared with 107 from Tertiary care center. All were assessed by the Psychiatrist using ICD-10 clinically after the informed consent. After 3 follow ups they were assessed with semi structured proforma, Indian Disability Evaluation and Assessment Scale (IDEAS), Global Assessment of Functioning (GAF), Patient Satisfaction Questionnaire Short Form (PSQ-18) instruments. Results: The Patient satisfaction was found to be higher in PHCs 83.07±8.72 compared to tertiary subjects 75.27±9.51 (p<0.05). Severe mental illness was higher 48.96% in PHCs as compared to tertiary care center common mental illness 23.36%. Subjects from tertiary care centres report higher GAF score (65%) higher among tertiary care subjects than their PHC counterparts (35%). Conclusions: The patients receiving treatment in PHC’s reported more satisfaction than those who receive treatment in tertiary care center. Higher disability scores on IDEAS in PHC’s than tertiary Center due reporting of more cases of severe mental illness in PHC’s. Married patients have shown higher satisfaction as compared to single/ Divorced/ Separated patients. Alcohol Dependence Syndrome was found to be more in tertiary care hospital than in PHC’s.